Light control & fault detection system with LoRa - Muhammad Taufiq Syed Mohamed Bukari (Nanyang Technological University, 2020)
with resources like water and energy as well increasing awareness of safety, security and efficiency are driving the need for more information and better options to connect and manage advance sensors to build a smarter world. The Internet of Things are rapidly gaining popularity around the world. Billions of physical devices that are now connected to the internet around the world, all of which gather and exchange information [1]. The prediction is that by 2020 there will be over 25 billion devices connected to the Internet [2]. You will be able to monitor and control any device that is connected to the internet. The Internet of Things is going to connect the world and it will create lots of efficiencies and new business opportunities. There are many wireless technologies you can use to connect these devices to the Internet, such as, short-range wireless communication, cellular communication and LPWAN communication. The aim of this project is to utilize LoRa technology to further enhance the current building management system to a fully wireless operated system. Additional feature such as light control and error control will be implemented. A virtual simulator will be created to simulate the real-life application. This simulation will then be used as a guide to implement the actual hardware application in the future.